Developing a Walkability Index for Built Environment and its Applications at Different Spatial Levels - Emad Dawwas; Ayah Helal (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
Walking is being widely recommended by the mainstream research about sustainable development as a preferable commuting mode for health, economic and environmental reasons. Therefore, designing and implementing walkable communities are increasingly becoming main goals adopted by urban planners and transportation engineers. Considering a wide range of walkability parameters, this study aimed to develop a quantification method of walkability based on the technical standardization. The study proposed a multi-component walkability index “PASS” that stands for the four measurable components of the index including: Physical design component (P); Aesthetic and convenience component (A); Safety component (S) and Special needs requirements (S). The PASS index was constructed using field data that was collected about 1418 road segments with overall length of 253.1 km in Nablus city, West Bank, Palestine. The value of the index ranges from 0 (the worst walking conditions) to 5 (the best conditions). A special Geographic Information Systems (GIS) tool was designed to accommodate the PASS index and to represent the results spatially. PASS was found to be an effective tool in quantifying and assessing walkability at four spatial levels: (1) road and road segment level; (2) road network level; (3) neighborhood and district level; and (4) city level. Therefore, decision-makers, planners, and engineers can benefit from the proposed methodology to identify where interventions are required and to prioritize budget allocation to improve the walking environment at all spatial levels. The proposed tool is a significant methodological contribution to the field of urban and city planning as it can be easily replicated in other cities with limited financial and technical resources.